Achievement Motivation for Professional Success of the Thai National Rugby Team - Aphirattananon, Chontipa; Yenyuak, Chalermporn (The Journal of Development Administration Research, 2022)
The purposes of this study were 1) to study demographic factors affecting career success of the Thai national rugby team, and 2) to study the achievement motivation affecting the career success of the Thai national rugby team. This study employed quantitative research methods. The samples of the study included 400 Thai national rugby players. These samples were selected using the accidental sampling method. The questionnaire was used to collect data from the samples. The statistics used in the analysis were frequency, percentage, average, standard deviation, multiple comparison, one-way ANOVA, and multiple linear regression. The results of the study found that 1) the majority of respondents were male. Age between 21 - 30 years old, bachelor's degree have an average monthly income of 15,001 – 25,000 baht and have been in rugby career for 2 – 5 years 2) The results of the analysis of information on achievement motivation factors revealed that Respondents gave their opinions on overall achievement motivation factors. at the highest level When considering each aspect, it was found that the questions with the highest average level were ambition, followed by enthusiasm. Self-responsibility and in terms of their own decision-making needs For the questions with a high average level, namely, diligence, respectively. The results from the hypothesis testing revealed that the demographic factors, including age and education background, affected the career success differently with a statistically significant level at 0.05. In addition, the demographic factors, including monthly income and experience in the field, affected the career success similarly. Concerning the achievement motivation factors, it was found that ambition, industriousness, self-responsibility, self-determination, and enthusiasm are all related to the career success of the Thai national rugby players with a statistically significant level at 0.05.